The ladies rewrite the rules - Allain, Suzanne (Berkley Romance, 2024)
"From the author of Mr. Malcolm's List comes a delightful romantic comedy set in Regency England about a widow who takes high society by storm. Diana Boyle, a wealthy young widow, has no desire to ever marry again. Particularly not to someone who merely wants her for her fortune. So when she discovers that she's listed in a directory of rich, single women she is furious, and rightly so. She confronts Maxwell Dean, the man who published the Bachelor's Directory, and is horrified to find he is far more attractive than his actions have led her to expect. However, Diana is unmoved by Max's explanation that he authored the list to assist younger sons like himself who cannot afford to marry unless it's to a woman of means. She gathers the ladies in the directory together to inform them of its existence, so they may circumvent fortune hunters' efforts to trick them into marriage. Though outraged, the women decide to embrace their unique position of power and reverse the usual gender roles by making the men dance to their tune. And together...the ladies rewrite the rules"--